The Implementation of Islamic Teachings Based on Local Wisdom: A Study of Pre-Islamic Arab Cultural Practices Adopted into Islamic Law - M. Munif (International Journal of Education Management and Religion, 2026)
The study aims to examine how certain pre-Islamic Arab cultural practices were legislated into Islamic teachings and how they continue to influence Islamic practices today. To achieve this, Islam established rules for carrying out daily activities based on the teachings of Allah SWT and His Messenger. However, this did not automatically erase all the pre-Islamic Arab culture and traditions; rather, the positive aspects were preserved and maintained by Islam as part of its teachings. The method used in this research is a library research with a qualitative descriptive approach, while data collection is carried out through documentation from books and journal articles, and data analysis is conducted using content analysis. The results of the study show several pre-Islamic Arab traditions and cultures that were legislated into Islamic teachings and are implemented by Muslims, including respecting guests, giving charity, keeping promises, trading, acquiring knowledge, and helping one another. These traditions and cultures are affirmed as part of Islamic teachings, supported by several verses of the Qur'an and hadiths to implement these practices.